Hugo Bettarello e a Agabê: da modernidade almejada aos calçados made in Brazil (1945-1980) - Silva, Rodrigo Mateus [UNESP] (2013)
The challenge in the achievement of a biographic work is not only in the revelation of the details of an individual trajectory. The individuals are not isolated elements of the reality that they lived. When working with the process of constitution of Agabê, which was founded in 1945, and analyzing the mishaps of Hugo Bettarello’s biography, there isn’t a restricted concerning in the recovered trajectories or in the surveys performed with a imprint memorialistic. The development process of the industrialization in Brazil is observed and the changings in the social relations are mentioned from the new urban reality imposed by industrialization. The rural exodus was encouraged and the market economy was changing the rural traditions that farmers brought to the urban environment. The domestic economic development was placed on the potential expansion of international capitalism. In this sense, interventionist economic policies were applied in order to promote industrialization, culminating in the policies of import substitution. Throughout the 1940s and 1950s developmentalism was associated with some distributive measures, aimed at creating a model of capitalism ruled by ideals of social equality. However, in the early 1960s the capitalist model implemented followed a different trajectory, in which the authoritarianism of the post-1964 and contributed to increased income concentration in Brazil. The prosopography of Agabê and analysis of the business career of Hugo Bettarello seeks to study this whole process of development of the industry in Brazil